Adaptive Motivation and Emotion in Education: Research and Principles for Instructional Design. (October 2016) - Linnenbrink-Garcia, Lisa; Patall, Erika A.; Pekrun, Reinhard
Students frequently experience various types of motivation and emotion that contribute to their engagement and learning. However, translating research on motivation and emotion into educational practice and policy has so far been limited. To facilitate greater synergy among research, practice, and policy, this overview addresses educationally relevant motivation and emotion. This summary discusses different forms of motivation or emotion, their relevant theoretical basis, evidence on how they relate to academic engagement and learning, and potential classroom supports for adaptive motivation and emotion. The article concludes with five instructional design principles that can guide educators and policymakers in promoting adaptive student motivation and emotion: (a) support students' feelings of competence, (b) enhance autonomy, (c) use personally relevant and active tasks, (d) emphasize learning and de-emphasize social comparison, and (e) encourage feelings of belonging.